Associations Between Preoperative Biomarkers and Cardiac Surgery–Associated Acute Kidney Injury in Elderly Patients: A Cohort Study. (September 2021) - Verwijmeren, Lisa; Bosma, Madeleen; Vernooij, Lisette M.; Linde, Esther M.; Dijkstra, Ineke M.; Daeter, Edgar J.; Van Dongen, Eric P. A.; Van Klei, Wilton A.; Noordzij, Peter G.
Abstract : BACKGROUND: Acute kidney injury (AKI) is associated with mortality after cardiac surgery. Novel risk factors may improve identification of patients at risk for renal injury. The authors evaluated the association between preoperative biomarkers that reflect cardiac, inflammatory, renal, and metabolic disorders and cardiac surgery–associated AKI (CSA-AKI) in elderly patients. METHODS: This was a secondary analysis of the 2-center prospective cohort study "Anesthesia Geriatric Evaluation." Twelve biomarkers were determined preoperatively in 539 patients. Primary outcome was CSA-AKI. The association between biomarkers and CSA-AKI was investigated with multivariable logistic regression analysis. Secondary outcomes were 1-year mortality and patient-reported disability and were assessed with relative risks (RR) between patients with and without CSA-AKI. RESULTS: CSA-AKI occurred in 88 (16.3%) patients and was associated with increased risk of mortality (RR, 6.70 [95% confidence interval CI, 3.38–13.30]) and disability (RR, 2.13 [95% CI, 1.53–2.95]). Preoperative concentrations of N-terminal pro B-type natriuretic peptide (NT-proBNP), high-sensitive C-reactive protein (hs-CRP), hemoglobin, and magnesium had the strongest association with CSA-AKI. Identification of patients with CSA-AKI improved when a biomarker panel was used (area under the curve [AUC] 0.75 [95% CI, 0.69–0.80]) compared to when only clinical risk factors were used (European System for Cardiac Operative Risk Evaluation [EuroSCORE II] AUC 0.67 [95% CI, 0.62–0.73]). CONCLUSIONS: Preoperative cardiac, inflammatory, renal, and metabolic biomarkers are associated with CSA-AKI and may improve identification of patients at risk.